Single-channel study of the spasmodic mutation α1A52S in recombinant rat glycine receptors - Plested, Andrew J R (Blackwell Science Inc, 2007)
Inherited defects in glycine receptors lead to hyperekplexia, or startle disease. A mutant mouse, spasmodic, that has a startle phenotype, has a point mutation (A52S) in the glycine receptor α1 subunit. This mutation reduces the sensitivity of the receptor to glycine, but the mechanism by which this occurs is not known. We investigated the properties of A52S recombinant receptors by cell-attached patch-clamp recording of single-channel currents elicited by 30–10000 μm glycine. We used heteromeric receptors, which resemble those found at adult inhibitory synapses. Activation mechanisms were fitted directly to single channel data using the HJCFIT method, which includes an exact correction for missed events. In common with wild-type receptors, only mechanisms with three binding sites and extra shut states could describe the observations. The most physically plausible of these, the ‘flip’ mechanism, suggests that preopening isomerization to the flipped conformation that follows binding is less favoured in mutant than in wild-type receptors, and, especially, that the flipped conformation has a 100-fold lower affinity for glycine than in wild-type receptors. In contrast, the efficacy of the gating reaction was similar to that of wild-type heteromeric receptors. The reduction in affinity for the flipped conformation accounts for the reduction in apparent cooperativity seen in the mutant receptor (without having to postulate interaction between the binding sites) and it accounts for the increased EC(50) for responses to glycine that is seen in mutant receptors. This mechanism also predicts accurately the faster decay of synaptic currents that is observed in spasmodic mice.